Soil Chemical Properties and Chilli (Capsicum Frustescens L) Yields Following Ameliorants derived from Taliwang Pond- Sidemen and Biocompost Application on the Dryland Farming System of Western Sumbawa, Indonesia - Azizah, Erlina; Fauzi, Taufik; Sukartono, Sukartono (International Journal of Environment, Agriculture and Biotechnology, 2019)
A field study was conducted to evaluate the effects of Taliwang Pond sidemen (TPS) and biocompost application on the soil chemical properties, growth performance and yield of chilli on the dryland farming system in Belo village, Jereweh Sub-district, Western of Sumbawa, Indonesia from February to May 2019. The experiment was set up using a Completely Randomized Design (CRD) consisted of two factors namely sidement (0 t ha-1 as S0 and 40 t ha-1 as S1) and biocompost (0 t ha-1 (K1), 10 t ha-1(K2), 20 t ha-1 (K3), 30 t ha-1(K4) and 40 t ha-1 as K5) with three replications. The results of study showed that the application of both TPS and biocompost improved soil fertility status (C, P and K) and increased growth and yields of chilli. It was recorded that the application of both TPS and biocompost at rates of 40 t ha-1 resulted in the highest yields of chille as results soil fertility improvement. The highest yied was reach two times as compared to the control (plot with no soil organic ammendement).